2007
DOI: 10.1158/0008-5472.can-06-1390
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Base Excision Repair Genes and the Prevalence of Advanced Colorectal Adenoma

Abstract: Base excision repair (BER) corrects DNA damage caused by oxidative stress and low folate intake, which are putative risk factors for colorectal neoplasia. To examine the relationship between genetic variation in BER genes and colorectal adenoma risk, we conducted a case-control study of 767 cases of advanced colorectal adenoma and 773 controls from the baseline screening exam of the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. Cases included participants diagnosed with advanced left-sided ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 48 publications
4
34
2
Order By: Relevance
“…Neither variant is likely to influence the activity of the protein itself: the T allele at Ala284Ala does not affect the amino acid sequence of the protein. Thus, our results supports Berndt et al (2007) findings in which they suspected that the association that we observed with colorectal adenoma may be due to linkage disequilibrium with another variant in the region, possibly in the PARP1 promoter. Because PARP1 activity is highly regulated by its promoter, variants within transcription binding sites in the promoter may influence its expression (Berndt et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Neither variant is likely to influence the activity of the protein itself: the T allele at Ala284Ala does not affect the amino acid sequence of the protein. Thus, our results supports Berndt et al (2007) findings in which they suspected that the association that we observed with colorectal adenoma may be due to linkage disequilibrium with another variant in the region, possibly in the PARP1 promoter. Because PARP1 activity is highly regulated by its promoter, variants within transcription binding sites in the promoter may influence its expression (Berndt et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our results supports Berndt et al (2007) findings in which they suspected that the association that we observed with colorectal adenoma may be due to linkage disequilibrium with another variant in the region, possibly in the PARP1 promoter. Because PARP1 activity is highly regulated by its promoter, variants within transcription binding sites in the promoter may influence its expression (Berndt et al, 2007). In a similar way Milani et al (2007) reported that PARP1 contains contain functional regulatory SNPs in their promoter regions and SNP rs1805414 expression level is effected by allelic imbalance in cancer cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The 194Trp variant has also been found to be protective against lung cancer, although it is associated with an increased risk of CRC [8]. The results for the Arg399Gln polymorphism of the XRCC1 gene in colorectal cancer epidemiology are very ambiguous [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The numbers reported by Shen et al for TT and TG/GG in controls were 70 and 52; while the numbers in Kasahara et al's original publication were 70 and 51. Also, the data reported by Shen et al for the study of Berndt et al [3] were not consistent with the data provided by Berndt et al in their original publication. The numbers reported by Shen et al for TT, TG, GG in cases and controls were 175-364-153 and 204-335-171; however, the numbers in their original publication for TT, TG, GG genotypes in cases and controls were 186-387-166 and 222-357-178, respectively.…”
Section: To the Editormentioning
confidence: 58%